Synthesis and Characterization of Novel Rutin Derivatives with Potential Antioxidant Properties - Mahitab H. El Bishbishy; Mohammed Abdalla Hussein (International Journal of Phytomedicine, 2019)
Rutin, a flavonol glycoside isolated from the fruit peels of Malus domestica family Rosaceae, is well known to possess antioxidant activity. This research was conducted in order to synthesize and characterize rutin derivatives and evaluate their antioxidant activities. Four derivatives were synthesized namely, Rutin-oxy-5, 7, 4' acetic acid (2), Rutin -oxy- 5,7, 4' methyl benzoate amide (3), 2'', 2''', 2''''-rutinoxymethyl-3-amino-1 -benzo[5,6-a] pyrimidine-4-one (4) and 5'', 5''', 5''''-tri-p-methoxybenzylideneamino-6-rutinoxy-benzo[5,6-a]-pyrimidin-4(5H)-one (5). Their structures were elucidated using different spectral data (Mass, IR and 1H, 13C NMR). The antioxidant activities of rutin and its derivatives were evaluated by reducing power, Fe+2 chelating, DPPH* and ferric thiocyanate FTC assays. In addition, the results were compared with natural and synthetic antioxidants, such as α- tocopherol, butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA) and trolox. Rutin and its derivatives were exhibited a strong reducing power, chelating activity on Fe2+ and free radical-scavenging. Antioxidant activity of rutin and its derivatives increased with increased concentrations. Total antioxidant activity of rutin, its derivatives and both standards decreased in the order of rutin > compound (5) > trolox > compound (2) > BHA > compound (4) > compound (3). This study showed that Rutin and its derivatives exhibited antioxidant activity in all tests and could be considered as a source of natural and synthetic antioxidants.